Methods of Composing and Conducting an Interactive Ethnographic Excursion in the Museum of an Educational Institution - Irina G. Kulikova; Fanis R. Akhmadullin (Publishing house "Sreda", 2020)
The methodological techniques for conducting an interactive ethnographic excursion in the museum of the educational institution are reviewed in the article. It has been hypothesized that the introduction of elements of interactivity and immersivity into the structure of an ethnographic excursion will allow for a stronger and deeper learning of the material of the excursion. In order to confirm the hypothesis, an analysis of theoretical material on the topic of the study was carried out, a modern view of the museum of the educational institution as an object for transmitting cultural experience, as a guardian of historical memory was revealed. Methods. The research was carried out using the following methods: analysis of theoretical material, survey of participants of the museum and pedagogical process in order to identify the most effective methods of functioning of the museum, modeling, involving organization of various formats of activity of the museum of the educational institution, as well as methods of empirical level - observation, description, experiment. The results of the study, given in the work, confirmed that unlike the traditional excursion, which involves passive participation of students, interactive excursions allow to involve students in active interaction with the guide, motivate them to "independent" study and consideration of exhibits of the museum. The survey of participants of the museum and pedagogical process confirmed that emotional immersion in the material of the excursion contributes to its better learning and memorization.